Some aspects of meat production in pig autochthonous genetic types. II. Rheological and colorimetric characteristics of muscles - Palazzo M.; Abbatiello M.; Terracciano M.; Barone C.M.A.; Colatruglio P.; Matassino D. (Tradition and innovation in Mediterranean pig production, 2000)
The research was carried out on 51 pigs, 30 castrated males and 21 whole females, belonging to Calabrese (n equal to 16), Cinta Senese (n equal to 8) and Siciliano (n equal to 27) autochthonous genetic types (AGT). The rheological characteristics were evaluated on muscle samples taken at dissection from the refrigerated carcass; the most important results showed that the genetic type, sex and muscle significantly affect almost all rheological characteristics considered. In particular: (i) in comparison with Siciliano, Calabrese provide more tender meat, which requires a lower chewing energy (P less than 0.01); furthermore, Calabrese meat has a lower springiness and is lighter than other two AGTs (P less than 0.01-0.001).; (ii) the meat from castrated males is rheologically better than that obtained from females: it is lighter, more tender, less springy with a lower cohesiveness, hence with a lower chewiness value (P less than 0.01-0.001); and (iii) the muscles display a great histochemical individuality: PM is more tender and requires a lower chewing energy (P less than 0.001), even though it shows a higher adhesiveness value; on the contrary, the ClaTB is the 'worst' muscle from a rheological point of view. As regards colorimetric characteristics, Ss is the 'lightest' muscle, because of its higher reflectance percentage at any considered wavelength and lightness (L asterisck); it was followed, in decreasing order, by LD, PM, CLaTB and CLoTB; the last being the 'darkest'.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)